Anabolic Activity of a Soy Extract and Three Major Isoflavones in C2C12 Myotubes - Zheng, Wenya; Hemker, Marie L.; Xie, Mingyong; Soukup, Sebastian T.; Diel, Patrick (Planta Medica, 2018)
Isoflavones have been reported to stimulate muscle growth. The aim of this in vitro study was to examine anabolic activity and associated molecular mechanisms of a soy extract (SoyEx), isoflavone aglycones, and a mixture simulating the composition of SoyEx in C2C12 myotubes. C2C12 cells were differentiated into myotubes. The effects of SoyEx, genistein, daidzein, glycitein, and the mixture of genistein-daidzein-glycitein (Mix) on myotube diameter and number were determined. In addition, the expression of genes and proteins associated with anabolic activity was analyzed. Treatment with SoyEx, genistein, and Mix led to a significant increase of myotube diameter and an increase of the number of myotubes per area compared to the control cell. The increase of diameter by SoyEx was antagonized by an antiestrogen, not by an antiandrogen. Furthermore, gene expressions of insulin growth factor (IGF)-1 and its receptor (IGF-1R), as well as protein expression of myosin heavy chain (MHC), were significantly increased by SoyEx, genistein, and Mix. The effects induced by genistein and Mix were comparable to SoyEx. In conclusion, SoyEx displays an anabolic activity in C2C12 myotubes by binding to ER and modulating IGF-1 and MHC expression. Our studies with isoflavone aglycones and Mix indicate that the isoflavone aglycone with the highest anabolic bioactivity in SoyEx is genistein.
Keywords: isoflavones; Glycine max; Leguminosae; C2C12 myotube; IGF-1; MHC